Knowledge, attitude, and perception of community pharmacists towards antimicrobial stewardship in Saudi Arabia: A descriptive cross-sectional study - Abdul Haseeb; Mahmoud Essam Elrggal; Mohammed Saeed Bawazir; Mohammed Omar Bawazir; Inayat Ur Rehman; Hani Saleh Faidah; Saleh Alghamdi; Ahmad J. Mahrous; Alaa Mutlaq; Muhammad Shahid Iqbal; Safa S. Almarzoky Abuhussain; Manal Algethamy; et al. (Elsevier, 2022)
Background: Antimicrobial resistance is of paramount concern globally. Community pharmacists (CPs) play a vital role in supporting judicious antimicrobial use in the community as they are the key healthcare providers at a public level. This study aimed to assess the knowledge, attitude, and perception of CPs towards antimicrobial stewardship at the community level in Saudi Arabia. Methods: A self-administered questionnaire was distributed to all community pharmacies in four major cities of Saudi Arabia. A simple random sampling approach was used to select pharmacies in each chain. Results: A total of 520 CPs responded to the survey with a response rate of 98.6 %. Most of the pharmacists (n = 479, 92.1 %) accepted that antimicrobial stewardship programs are essential tools to limit injudicious usage of antimicrobials at the community level. Interestingly, very few (n = 105, 21 %) agreed to recommend antibiotics for common illnesses, including upper respiratory tract infections, cold, and flu without a valid prescription. Further, we found a significant role of Saudi health authorities, e.g., Saudi food & drug authorities and the Ministry of Health, in restricting antimicrobials sale in community pharmacies without a valid prescription. Conclusion: Our study findings revealed that CPs had good knowledge about antimicrobial stewardship in Saudi Arabia. The CPs play an active role in the optimization of antimicrobial therapy and infections caused by different microbes. Strict policies by the Saudi health care authority regarding the restricted dispensing of antimicrobials are welcomed by the CPs and thus may contribute toward lowering of antimicrobial resistance burden on the patients and Saudi health care authorities.